An Improved and Privacy-Preserving Mutual Authentication Scheme with Forward Secrecy in VANETs. (21st April 2021) - Yao, Mengting; Wang, Xiaoming; Gan, Qingqing; Lin, Yijian; Huang, Chengpeng
Abstract : Vehicular ad hoc network (VANETs) plays a major part in intelligent transportation to enhance traffic efficiency and safety. Security and privacy are the essential matters needed to be tackled due to the open communication channel. Most of the existing schemes only provide message authentication without identity authentication, especially the inability to support forward secrecy which is a major security goal of authentication schemes. In this article, we propose a privacy-preserving mutual authentication scheme with batch verification for VANETs which support both message authentication and identity authentication. More importantly, the proposed scheme achieves forward secrecy, which means the exposure of the shared key will not compromise the previous interaction. The security proof shows that our scheme can withstand various known security attacks, such as the impersonation attack and forgery attack. The experiment analysis results based on communication and computation cost demonstrate that our scheme is more efficient compared with the related schemes.